Operating efficiency and output insensitive employment contracts for capital management - Noe, T; Nachman, D (1995)
This paper considers a problem in which an agent is hired to manage a capital investment and subsequently receives private information regarding the productivity of the capital investment. The capital manager must decide whether to invest capital supplied by the firm (the principal), or to divert these investment funds to perquisite consumption. If the manager decides to invest, the manager must then select the level of operating efficiency (productivity) of the capital investment, this latter choice being unobservable and constrained by the (maximal) productivity of the investment. In this setting we demonstrate that the optimal employment contract, from the perspective of the firm hiring the manager, is the contract whichminimizes the dependence of the manager's compensation on firm output. This contract pays the manager a fixed wage whenever output from the investment exceeds the wage and provides the manager with all of the projects rents whenever output falls below this level. Thus, we provide a setting in which fixed wage contracts are the optimal incentive contract even when agents are risk neutral and contracts can be costlessly written on future output.